Provision of medical assistance to military personnel and civilians in clinical institutions of the National Academy of Medical Sciences of Ukraine during the ATO/JFO - Tsymbalyuk, V. I.; Lurin, I. A.; Zhakhovskiy, V. O.; Livinskiy, V. G.; Shvets, A. V. (Medicni Perspektivi, 2020)
Purpose – analysis and generalization of the experience of the National Academy of Medical Sciences (NAMS) of Ukraine and its subordinate research institutions, with clinical units in their structure, on the provision of highly specialized medical care to the wounded, injured, injured and sick servicemen during the anti-terrorist operation and the operation of the Joint Forces (ATO/JFO), as well as the civilian population and internally displaced persons from the temporarily occupied territories. The object of the research is the health care system of military personnel.The subject of the research is the work of the National Academy of Medical Sciences of Ukraine on the organization and provision of medical assistance to military personnel and civilians during the ATO/JFO.Research methods: bibliographic, statistical, analytical, systems approach. The NAMS of Ukraine and its subordinate research institutions, with clinical units in the structure, during the ATO/JFO took an active part in the provision of medical care to the wounded, injured, injured and sick servicemen of the Armed Forces of Ukraine and other military formations. The work of the NAMS of Ukraine in providing medical assistance to servicemen was multi-vector and was carried out in several directions: organizational, direct provision of medical care and its scientific support. Clinical institutions of the NAMS of Ukraine during the ATO/JFO did not stop providing highly specialized medical care to the civilian population of Ukraine, including internally displaced persons from the areas of the ATO/JFO. Thanks to the coordinated activities of the Presidium of the NAMS of Ukraine and its subordinate research institutions, a significant contribution has been made to the provision of highly specialized medical care to the wounded, injured and sick servicemen, as well as internally displaced persons from the temporarily occupied territories.